Schooling and institution quality linked to earnings in the Eastern Cape - Cuthbert, Carol E (Rhodes University, Faculty of Commerce, Rhodes Business School, 2018)
Return to investment for tertiary education is not equal for all. Human Capital Theory imposes a linear pathway between education and earnings, that fails to recognise other sources of capital, ignores social returns and does not explain why socio-economic variables influence employability and earnings. Those returns, rather than simply incrementally delivering returns for additional years of education, are however heterogeneous across students, with field of study, gender and population group influencing earnings; and schooling type and university attended filtering whether one finds a job. This study utilises data from Rhodes University and the University of Fort Hare, illustrating the extreme positions within the South African education landscape, employing a Heckman selection to predict the returns on education. The regression is found to be partially successful in predicting a graduate's ability to find a job, in the first instance, and thereafter their returns. It is crucial to analyse the heterogeneity of socio-economic parameters to understand aspects of the economy, and develop education policies to take advantage of this understanding, especially against the backdrop of the student protests being experienced in the country and the funding models proposed. Access to tertiary education, through policy inducement, such as the recent increase of the grant limit from R122 000 to R350 000, requires disaggregated returns to education to be investigated.
Keywords: Wages -- Effect of education on -- South Africa -- Eastern Cape; Education, Higher -- Economic aspects -- South Africa -- Eastern Cape; Equality -- South Africa -- Eastern Cape